Marketing Extension Gardening Publications in Boise Nurseries and Garden Centers in 1994 and 1995 - Marlene A Fritz; Susan M Bell (Journal of Applied Communications, 1997)
Six Boise, Idaho, garden centers began selling University of Idaho extension gardening publications in spring, 1994, on 20-slot metal racks provided by the Agricultural Communications Center (ACC).